Accurate Reading with Sequential Presentation of Single Letters - Price, Nicholas S.; Edwards, Gemma L. (Frontiers in Neuroscience, 2012)
Rapid, accurate reading is possible when isolated, single words from a sentence are sequentially presented at a fixed spatial location. We investigated if reading of words and sentences is possible when single letters are rapidly presented at the fovea under user-controlled or automatically-controlled rates. When tested with complete sentences, trained participants achieved reading rates of over 60 words/minute and accuracies of over 90% with the single letter reading (SLR) method and naive participants achieved average reading rates over 30 wpm with >90% accuracy. Accuracy declined as individual letters were presented for shorter periods of time, even when the overall reading rate was maintained by increasing the duration of spaces between words. Words in the lexicon that occur more frequently were identified with higher accuracy and more quickly, demonstrating that trained participants have lexical access. In combination, our data strongly suggest that comprehension is possible and that SLR is a practicable form of reading under conditions in which normal scanning of text is not possible, or for scenarios with limited spatial and temporal resolution such as patients with low vision or prostheses.